BPJS Employment Development Strategy for Ternate Branch in Increasing Acquisitions for Shield Agents - Mohbir Umasugi; Ridho Harta (GoAcademica Research & Publishing, 2023)
Social security is a form of social protection that guarantees everyone can fulfill a decent life's basic needs. Having death and accident insurance while working is very important for all non-formal workers in Indonesia, including in the city of Ternate and its surroundings. The data analysis method used in this research is descriptive qualitative. Qualitative descriptive is a method used to explore findings in the field. The research results show that there are four successful shield builders, such as the shield office built by Muhammad Hikmawan, which has 24 shield agents; Prasanti D has 25 shield agents; Taufik Hariyadi has 26 shield agents; and Vincenzo Runtu has 26 shield agents. The total number of agents from 4 supervisors is 101 productive shield agents who help socialize the benefits of the BPJS Employment program to the working community, non-wage earners. New BPJS Employment participants with the non-formal worker segment include motorcycle taxi drivers, fishermen, fishermen traders, etc. The acquisition sequence for January, there were 1048 participants; in February, there were 744 participants; in March, there were 5328 participants; in April, there were 2022 participants; in May, there were 7497 participants; and in June, there were 7188 participants; the total number of new participants registered through shield agents from January to June was 23827 participant.